The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jace.14305
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Free Synthesis of Porous Fe3O4/SiOC(H) Nanocomposites with Enhanced Catalytic Activity

Abstract: We present a template‐free synthesis of Fe3O4/SiOC(H) nanocomposites with in situ formed Fe3O4 nanoparticles with a size of about 50 nm embedded in a nanoporous SiOC(H) matrix obtained via a polymer‐derived ceramic route. Firstly, a single‐source precursor (SSP) was synthesized by the reaction of allylhydridopolycarbosilane (AHPCS) with Fe‐acetylacetonate [Fe(acac)3] at 140°C. The SSP was heat‐treated at 170°C to generate Fe3O4 nanocrystals in the cross‐linked polymeric matrix. Subsequently, the SSP was pyroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
(115 reference statements)
6
12
0
Order By: Relevance
“…This result indicates that SMP‐10 reacted with MoO 2 (acac) 2 consuming Si‐ H groups. As for the reaction of polycarbosilane with metal acetylacetonates, it has been confirmed to form Si‐O‐M bonds by our previous work . In this study, as shown in Figure B, the new absorption band at 950 cm −1 is assigned to the formed Si‐O‐Mo unit …”
Section: Resultssupporting
confidence: 78%
“…This result indicates that SMP‐10 reacted with MoO 2 (acac) 2 consuming Si‐ H groups. As for the reaction of polycarbosilane with metal acetylacetonates, it has been confirmed to form Si‐O‐M bonds by our previous work . In this study, as shown in Figure B, the new absorption band at 950 cm −1 is assigned to the formed Si‐O‐Mo unit …”
Section: Resultssupporting
confidence: 78%
“…After annealing of the reaction mixture at 170°C for 2 hours, the reaction between SMP-10 and MoO 2 (acac) 2 results in the formation of Si-O-Mo bonds (950 cm −1 ) by consuming Si-H groups (2136 cm −1 ) of SMP-10, which has been discussed in our previous studies. 49 Besides, as compared with pure SMP-10 and DVB, the characteristic peaks of C = C (1627 cm −1 ) in SM/Mo/PS/DVB 2-1-4-2 disappear ( Figure 1B and previous studies, 49,50 an idealized reaction scheme is shown in Figure 1C.…”
Section: Characterization Of the Synthesized Single-source Precursorsupporting
confidence: 50%
“…PS as the pore former without functional groups cannot be involved in the chemical reaction between SMP‐10, MoO 2 (acac) 2 , and DVB. Based on the FT‐IR results and previous studies, an idealized reaction scheme is shown in Figure C.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer-derived ceramic (PDC) approach started from the 1960s and is a versatile method used for the fabrication of mainly Si-based advanced ceramics [1,2]. During the past 60 years, due to their physical-micro/mesoporous ceramics as catalyst supports with high specific surface area (SSA) and outstanding corrosion stability [14,[19][20][21][22].…”
Section: Introduction mentioning
confidence: 99%